Use of null models to explain crustacean zooplankton assemblages in waterbodies of Alerce Andino National Park (41°S, Chile) - De los Ríos-Escalante, Patricio; Hauenstein, Enrique; Romero-Mieres, Mario; Acevedo, Patricio (Crustaceana, 2012)
The zooplankton assemblages in deep, mostly oligotrophic northern Patagonian lakes are characterized by low species numbers and a marked dominance of calanoid copepods. In the present study, data collected in field work on six water bodies located in Alerce Andino National Park (41°S) were analysed using the Jaccard Index of community similarity and a co-occurrence of null models, and such with the aim of determining potential regulating factors for the observed crustacean assemblages, using a presence-absence matrix. A significant correlation between species number and surface area was found. The null model used species co-occurrence, and the basis of this model is that the species associations observed are random. The results revealed the absence of regulating factors and indicate that the sites are relatively homogeneous, with low species numbers and similar plankton assemblages at all studied sites. This finding is in accordance with similar descriptions for zooplankton assemblages in other Chilean Patagonian lakes. Los ensambles zooplanctónicos en lagos del norte de la Patagonia se caracterizan por su bajo número de especies y marcada dominancia de copépodos calanoideos. En el presente trabajo se colectaron datos de seis cuerpos de agua del Parque Nacional Alerce Andino, los cuales se analizaron usando un índice de similitud de comunidades de Jaccard y un modelo nulo de co-ocurrencia y con el mismo se determinaron los factores reguladores potenciales para explicar los ensambles zooplanctónicos usando una matriz de presencia y ausencia de especies. Este modelo nulo usó la co-ocurrencia de especies y parte de la base que las asociaciones de especies son aleatorias. Se observó una asociación significativa entre número de especies y superficie. Los resultados obtenidos indican la ausencia de factores reguladores en la mayoría de los análisis, lo que se debería a que los sitios son homogéneos, y al bajo número de especies reportadas las que además presentaron pocas especies repetidas en prácticamente todos los sitios estudiados. Estos resultados coinciden con descripciones similares para ensambles zooplanctónicos para otros lagos y lagunas de la Patagonia chilena.